Implementasi Media Pembelajaran Matematika Berbasis Augmented Reality pada Materi Transformasi Geometri di SMA Insan Cendekia Syech Yusuf Gowa - Abbas, Baharuddin; Amin, Badaruddin; Ibrahim; Sudarmin; Muhammad Rizki; Muh. Nur Hidayat; Masnaeni (Faculty of Tarbiyah and Teacher Training, 2025)
Augmented Reality (AR) is an innovative technology that is able to present three-dimensional virtual objects in the real world, thus providing an interactive learning experience. AR-based learning media has the potential to help students understand abstract concepts in geometry transformation more clearly and interestingly. This community service aims to facilitate the learning process of students on geometry transformation material using Augmented Reality (AR) based learning media. The activity was carried out at Insan Cendekia Syech Yusuf High School with three main stages, namely the preparation, implementation, and evaluation stages. In the preparation stage, AR learning media development and preparation of learning tools were carried out. The implementation stage includes the introduction of the concept of geometric transformation and direct practice of using AR learning media by students. The evaluation stage was carried out with learning outcome tests and questionnaires to measure the effectiveness and learners' responses to the activities. The evaluation results showed that the average learning outcomes of learners were 74, with a good category. In addition, the average learner response to the implementation of mentoring is 72.36, which is included in the positive category. These findings indicate that AR-based learning assistance can make a positive contribution to learners. Thus, learning assistance using AR-based learning media is feasible to be applied in learning mathematics.